2022
DOI: 10.1002/ctm2.989
|View full text |Cite
|
Sign up to set email alerts
|

Cancer‐associated fibroblast‐derived exosomal microRNA‐20a suppresses the PTEN/PI3K‐AKT pathway to promote the progression and chemoresistance of non‐small cell lung cancer

Abstract: 1. CAFs-derived exosomal miR-20a promotes the progression of NSCLC.2. CAFs-derived exosomal miR-20a promotes chemoresistance of NSCLC. 3. PTEN is a target gene of miR-20a. 4. miRNA-20a suppresses the PTEN/PI3K-AKT pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 76 publications
0
42
0
Order By: Relevance
“…qRT-PCR analysis showed the decreased expressions of ZEB, FGF2, SMAD4, KLF4 and PTEN in SKM1-miR92a1 and SKM1-miR92a2 cells ( Figure 3 B). Among these five genes, PTEN expression significantly decreased and it was reported to correlate with drug resistance [ 15 , 25 ]. Therefore, we aimed at PTEN as the potential target of miR92a ( Figure 3 B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…qRT-PCR analysis showed the decreased expressions of ZEB, FGF2, SMAD4, KLF4 and PTEN in SKM1-miR92a1 and SKM1-miR92a2 cells ( Figure 3 B). Among these five genes, PTEN expression significantly decreased and it was reported to correlate with drug resistance [ 15 , 25 ]. Therefore, we aimed at PTEN as the potential target of miR92a ( Figure 3 B).…”
Section: Resultsmentioning
confidence: 99%
“…Next, the TCGA database indicated increased expression of β-catenin in AML samples ( n = 173) compared to HD ( n = 70) ( Figure 4 C). Interestingly, when SKM1 and ML1 were incubated with a selective inhibitor of β-catenin, MSAB [ 15 ], the apoptosis of Exos-miR92a1/2-treated recipient cells was increased significantly compared to Exos-SKM1, which revealed that MSAB treatment reversed the Ara-C resistance of SKM1 and ML1 caused by Exos-miR92a1/2 ( Figure 4 D and Figure S3D ). Together, these data indicate that exosomal miR92a mediates the Ara-C resistance of SKM1 via inhibiting PTEN and activating β-catenin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PTEN/PI3K/AKT axis is reported to implicate in diverse physiological and pathological conditions and plays an important role in the regulation of cell growth and apoptosis in diverse human cancer including prostate cancer, hepatocellular carcinoma, and pancreatic cancer [41][42][43][44]. As the key target of PTEN, PTEN is identified to negatively regulate PI3K/AKT signaling [45,46]. Based on the regulation relationship between PTEN and PI3K/AKT signaling, we speculated that the effect of miR-2a-3p/PTEN regulation axis in laryngocarcinoma might be also mediated by PI3K/ AKT signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Protein lysates were obtained according to the previously described procedures ( 21 ). BCA1-1KT kit was used for the protein quantification assay.…”
Section: Methodsmentioning
confidence: 99%